2019
DOI: 10.31557/apjcp.2019.20.5.1571
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of SFRP1 Gene Promoter Methylation in Colorectal Carcinoma

Abstract: Background:The development of colorectal carcinoma (CRC) involves many genetic and epigenetic alterations and methylation being an important epigenetic event has been described as a diagnostic and prognostic biomarker. Secreted Frizzled- Related Protein 1 (SFRP1) gene regulates diverse physiological processes via the Wnt signaling. Promoter hypermethylation of SFRP1 gene is an epigenetic regulation mechanism that downregulates SFRP1 protein level in the tumor, and happens to be one of the significant events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…A recent study by Kumar et al showed promoter methylation of SFRP1 is associated with lymph node metastasis and poor mean overall survival (OS) in CRC. The majority of CRC samples in this study are methylated at SFRP1 with 72.2% methylation frequency [99]. On the contrary, Liu and colleagues postulated that the co-hypermethylation of SFRP1 and SFRP2 were suggested as independent prognostic predictors of survival advantage in postoperative CRC patients [100], whereby silencing of SFRP1 and SFRP2 by hypermethylation lead to a better prognosis.…”
Section: Sfrp1 and Disease Prognosismentioning
confidence: 58%
“…A recent study by Kumar et al showed promoter methylation of SFRP1 is associated with lymph node metastasis and poor mean overall survival (OS) in CRC. The majority of CRC samples in this study are methylated at SFRP1 with 72.2% methylation frequency [99]. On the contrary, Liu and colleagues postulated that the co-hypermethylation of SFRP1 and SFRP2 were suggested as independent prognostic predictors of survival advantage in postoperative CRC patients [100], whereby silencing of SFRP1 and SFRP2 by hypermethylation lead to a better prognosis.…”
Section: Sfrp1 and Disease Prognosismentioning
confidence: 58%
“…According to the literature, epigenetic remodeling of several genes ( KRAS, APC, p53, DCC, genes of the Rho family of GTPases, MACC1, Met, MTA1, RASSF1A, SFRP1 , etc.) are associated with malignant cellular transformation, progression, invasion, and metastasis in colorectal cancers [5,6,7]. Consequently, aberrant DNA methylation also offers an opportunity for its exploitation as ideal biomarkers for CRC prediction, diagnosis, and prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Galamb et al also proposed that hypermethylation of the SFRP1 promoter was associated with aging [35]. Kumar et al reported that SFRP1 promoter methylation was associated with lymph nodes metastasis [19]. Bartak discovered that the SFRP1 methylation was not connected with lymph node metastasis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Rawson et al discovered that SFRP1 methylation was not associated with recurrence-free survival in two large populations of CRC patients [18]. However, Kumar et al found that promoter hypermethylation of SFRP1 might be related to the poor prognosis of CRC [19]. Tang et al revealed that promoter methylation of SFRP2 in CRC tissues could be used as an independent prognostic factor for overall survival [20].…”
Section: Introductionmentioning
confidence: 99%